Compensating differentials for the risk of reinjury - lessons from professional boxing - Anderson, P. (Journal of Sports Economics, 2025)
A neglected area in the compensating-differential literature is how wages compensate workers for the risk of reinjury, specifically the risk of a subsequent mild Traumatic Brain Injury (mTBI). Using a new, unbalanced panel of 1,211 professional boxers, this paper finds that boxers' purses price for the risk of knockout reinjury risk while those that have never lost by knockout earn economically and statistically insignificant knockout-risk premiums. These results are consistent across three measures of previous knockout loss and three robustness tests, implying that current values of a statistical injury (VSI) underestimate previously injured workers' willingness to pay for safety.